2020
DOI: 10.29252/jorjanibiomedj.8.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Epidemiology of Cutaneous Leishmaniasis in Golestan Province, Northeastern Iran: A Systematic Review

Abstract: Background and objective: zoonotic cutaneous leishmaniasis (ZCL) is one of the most important health problems in Golestan Province, northeastern Iran. Several studies have investigated various aspects of the disease in this province. Herein, we provide a detailed review of the results of all studies related to leishmaniasis to give a reliable insight into the state of the disease in this province. Methods: The search for articles was performed in PubMed, Scopus, and Web of Science without language restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Shirzadi et al in a study that included provinces in the east and northeast of Iran showed a significantly positive relationship between CL incidence and land surface temperature (47). Mozafari et al (48) reported that the maximum temperature of the warmest month and mean temperature of the warmest and driest quarters have the highest contribution to the distribution of the disease in the Golestan province. Various studies have confirmed that higher maximum temperature, lower rainfall, and lower relative humidity are effective factors in the geographic distribution of leishmaniasis, especially in semi-arid areas of central Iran (47, 49, 50).…”
Section: Discussionmentioning
confidence: 99%
“…Shirzadi et al in a study that included provinces in the east and northeast of Iran showed a significantly positive relationship between CL incidence and land surface temperature (47). Mozafari et al (48) reported that the maximum temperature of the warmest month and mean temperature of the warmest and driest quarters have the highest contribution to the distribution of the disease in the Golestan province. Various studies have confirmed that higher maximum temperature, lower rainfall, and lower relative humidity are effective factors in the geographic distribution of leishmaniasis, especially in semi-arid areas of central Iran (47, 49, 50).…”
Section: Discussionmentioning
confidence: 99%
“…The only area where the Indian desert jird is found is Sistan and Baluchistan. The female sandfly Phlebotomus papatasi spreads the virus, and it has been reported in different provinces of Iran, including Fars, Isfahan, Khuzestan, Yazd, Semnan, Ilam, Golestan, and North Khorasan (51)(52)(67)(68)(79)(80)(81)(82)(83)(84)(85)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)14,31,48,62,65,71,75).…”
Section: Zoonotic Cutaneous Leishmaniasis (Zcl) Is a Serious Health I...mentioning
confidence: 99%
“…Further, various studies conducted in the province showed the CL incidence equal to 31.7 per 100,000 people. among them, the two counties of Gonbad-e Kavus and Maraveh Tappeh located in the northeast of the province had the highest incidence rates of 153 and 117 per 100,000 people ( 13 ). During 2010 – 2017, 360 – 1766 people from all age and gender groups in the province were infected with CL annually ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other regions of the province, the vectors and reservoirs of the disease are more abundant in the northeastern region of the province and the disease has higher incidence. These differences could be reasons for the geographical and climatic susceptibility of the region to a higher prevalence of the disease ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%